2009
DOI: 10.1007/s10461-009-9569-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Determinants of Consistent Condom Use by Partner Type Among Young Injection Drug Users: The Role of Personal and Partner Characteristics

Abstract: We investigated the longitudinal influence of individual-, relationship-and social-level factors on condom use by partner type among young injections drug users (IDUs) enrolled in the Collaborative Injection Drug Users Study-III/ Drug Users Intervention Trial (CIDUS-III/DUIT) from 2002 to 2004. Based on longitudinal analysis using generalized estimating equations (GEE), consistent condom use with main partners was more commonly reported among males and those with greater self-efficacy for condom use; main part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
(46 reference statements)
3
18
0
1
Order By: Relevance
“…Self-efficacy was a strong predictor for condom use. We may assume that it is temporally primary to the target behavior, a finding, which is confirmed by the existing literature on self-efficacy (Bandura, 1997) using longitudinal study designs in various populations (Grossman et al, 2008;Kapadia et al, 2009;Zimmerman et al, 2007). A further limitation of this study was the convenience sampling.…”
Section: Discussionsupporting
confidence: 61%
“…Self-efficacy was a strong predictor for condom use. We may assume that it is temporally primary to the target behavior, a finding, which is confirmed by the existing literature on self-efficacy (Bandura, 1997) using longitudinal study designs in various populations (Grossman et al, 2008;Kapadia et al, 2009;Zimmerman et al, 2007). A further limitation of this study was the convenience sampling.…”
Section: Discussionsupporting
confidence: 61%
“…However, some qualitative data indicated that this relationship may be a consequence of a high prevalence of unsafe sexual behaviors among IDUs rather than factors specific to prescription drug misuse. Quantitative research of young IDUs who primarily inject heroin and/or cocaine indicates that infrequent condom use is typical (Kapadia et al 2011). Hence, it is unknown whether the effects of prescription drug misuse influenced decisions about condom use during sex or whether risky sexual behaviors were simply common among IDUs irrespective of drug use.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may reflect factors contributing to differences by gender, such as the role of intimate partner violence, sexual risk reduction self-efficacy and partner-level factors (Somlai et al, 2003; Kapadia et al, 2007; Engstrom et al, 2011; Kapadia et al, 2011). Recent heroin and alcohol use were also associated with non-condom use in our study, which is consistent with existing literature (Metzger et al, 1993; Kalichman et al, 2002; Des Jarlais et al, 2007; Theall et al, 2007).…”
Section: Discussionmentioning
confidence: 94%